2018
DOI: 10.1038/s41372-017-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

Selenium: implications for outcomes in extremely preterm infants

Abstract: Extremely preterm infants are at high risk for morbidities including bronchopulmonary dysplasia, intraventricular hemorrhage, and retinopathy of prematurity likely related to their exposure to reactive oxygen and nitrogen species early in life. Selenium is a trace mineral contributes to the proper function of multiple systems including immunity, redox regulation, and inflammation via the "selenoenzymes" glutathione peroxidase, thioredoxin reductase, and selenoprotein P. Given that selenium accretion via the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Se contributes to the proper immune, redox, inflammatory, and thyroid function [2] . For an in depth review of the implications of perinatal Se deficiency on neonatal outcomes, the reader is referred to a recent publication by our group [5] . Perinatal Se deficiency is primarily driven by a lack of adequate placental transfer and insufficient postnatal Se supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se contributes to the proper immune, redox, inflammatory, and thyroid function [2] . For an in depth review of the implications of perinatal Se deficiency on neonatal outcomes, the reader is referred to a recent publication by our group [5] . Perinatal Se deficiency is primarily driven by a lack of adequate placental transfer and insufficient postnatal Se supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium (Se) is a trace element that is essential for proper redox signaling, antioxidant defense, and immune response in the critically ill patient [2] . During critical illness, low Se levels have been identified in neonatal, pediatric, and adult patients [3] , [4] and preterm infants are Se deficient at birth [5] . Low serum Se levels in patients with respiratory disease correlate with poor prognosis [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms of exposure to hyperoxia and inflammation which increases ROS could impact the mechanisms leading to premature birth. However, regardless of year of intensive research, the roles of Se, GPx, and selenoproteins are poorly understood in prematurity as well as oxidant injury [ 21 ]. In order to clearly be able to claim the role of trace elements in pre-term birth, roles of heavy metals should additionally be evaluated such as cadmium (Cd), which was found to be positively associated with the risk of early pre-term birth [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy represents a physiological state, which is considered to be a time of increased oxidative stress and in order to protect the fetus, the maternal antioxidants need to work against free radicals in utero [ 21 ]. During pregnancy, especially pre-eclamptic women, who often exhibit SGA newborns, have reduced placental GPx activity compared to control women [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, many studies have reported the association between gene polymorphisms and T2DM risk. Selenium is an essential trace element in mammals, which contributes to the normal functioning of multiple systems, including immunity, redox regulation, and resistance to inflammation, through "selenide" glutathione peroxidase and thioredoxin reductase . Currently, it has been found that selenoprotein gene polymorphism is closely associated with inflammatory and immune diseases.…”
Section: Introductionmentioning
confidence: 99%